2009
DOI: 10.1111/j.1532-5415.2009.02554.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Tobacco, and Nonmedical Drug Use in Older U.S. Adults: Data from the 2001/02 National Epidemiologic Survey of Alcohol and Related Conditions

Abstract: Objectives To examine the prevalence and sociodemographic and health-related correlates of substance use, including alcohol, tobacco and non-medical drug use, among adults aged 65 years and older. Design Cross-sectional, retrospective survey of a population-based sample, the 2001-02 National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) Setting United States Participants Eight thousand two hundred and five US adults aged 65 years of age and older. Measurements Prevalence of lifetime and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 19 publications
11
70
0
Order By: Relevance
“…Some findings such as divorced or separated (Moore et al, 2009) for daily current tobacco use and female gender for the inability to quit smoking (Agrawal et al, 2008) were in agreement with other studies. Unlike in some other studies (Kim et al, 2007;Hirayama et al, 2008;Moore et al, 2009, Peer et al, 2009Malawi (Ministry of Health [Malawi] and World Health Organisation, 2010;Negin et al, 2011;Blazer & Wu, 2012) , this study did not find any effect of gender and age on current daily Tobacco Use in Older Adults 285 tobacco use. Since more men than women quit tobacco use before reaching older age, it seems similar rates of tobacco use between older men and women persist.…”
Section: Discussionsupporting
confidence: 84%
“…Some findings such as divorced or separated (Moore et al, 2009) for daily current tobacco use and female gender for the inability to quit smoking (Agrawal et al, 2008) were in agreement with other studies. Unlike in some other studies (Kim et al, 2007;Hirayama et al, 2008;Moore et al, 2009, Peer et al, 2009Malawi (Ministry of Health [Malawi] and World Health Organisation, 2010;Negin et al, 2011;Blazer & Wu, 2012) , this study did not find any effect of gender and age on current daily Tobacco Use in Older Adults 285 tobacco use. Since more men than women quit tobacco use before reaching older age, it seems similar rates of tobacco use between older men and women persist.…”
Section: Discussionsupporting
confidence: 84%
“…9 25 specifically examined adults aged 65þ (n ¼ 8205) in the 2000-01 NESARC; 3.5% of the sample reported any lifetime use of illicit or nonmedical drugs and 1.1% reported any past-year use of illicit or nonmedical drugs. In addition, only 0.6% of adults aged 65þ had a lifetime drug use disorder (cannabis, 0.21%; opioids, 0.16%; tranquillizers, 0.13%; amphetamine, 0.11%; sedatives, 0.07%), and 0.2% had a past-year drug use disorder.…”
Section: Drug Use Disordersmentioning
confidence: 99%
“…Alcohol is the substance of choice among older Americans (Moore et al, 2009), and while alcohol use declines overall as we age (Moos, Schutte, Brennan, & Moos, 2009), the 2001/2002 National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) revealed that among adults aged 65 years and older, 45% had used alcohol in the past year (Moore et al, 2009). The estimated prevalence of AUDs among individuals 65 years and older ranges from 1% to 9% in the general population (e.g., Grant et al, 2004;Thomas & Rockwood, 2001), and 10% to 15% among older adults presenting to hospital emergency rooms (e.g., Adams, Magruder-Habib, Trued, & Broome, 1992).…”
Section: Introductionmentioning
confidence: 99%